Coupling Zn2+ Ferrying Effect With Anion–π Interaction to Mitigate Space Charge Layer Enables Ultra‐High Utilization Rate Zn Anode - Zhang, Zhaoyu; Lan, Xiaojia; Liao, Guoli; Du, Wencheng; Zhang, Yufei; Ye, Minghui; Wen, Zhipeng; Tang, Yongchao; Liu, Xiaoqing; Li, Cheng Chao (Angewandte Chemie International Edition, 2025)
A major dilemma faced by Zn anodes at a high zinc utilization rate (ZUR) is the insufficient supply of ionic carriers that initiate the space charge layer (SCL) subject to the rampant growth of Zn dendrites. Herein, an “anion–cation co‐regulation” strategy, associated with a fundamental principle for screening potential electrolyte additives coupling the Zn2+ ferrying effect with anion‐retention capability, is put forward to construct dendrite‐free, high‐ZUR Zn anode. Taking ninhydrin‐modified ZnSO4 system as a proof‐of‐concept, the multiple zincophilic polar groups of ninhydrin facilitate the transport of Zn2+ ions, while its electron‐deficient aromatic ring retains SO42− counterions via anion–π interaction, constructing an ion‐rich interface that minimizes the SCL‐driven Zn deterioration. Consequently, the Zn anode can endure ∼240 h continuous cycling at an ultrahigh ZUR of 87.3%. The superiority brought by ninhydrin is further reflected by the ultralong cycling durability of Zn‐I2 batteries (over 100 000 cycles). Even at an ultralow N/P ratio of 1.1 (∼90.6% ZUR), the battery with a capacity of ∼5.27 mAh cm−2 can still sustain for 350 cycles, which has been hardly achieved in aqueous Zn batteries. Furthermore, the effectiveness of this strategy is fully validated by a series of additives sharing similar fundamentals. An “anion–cation co‐regulation” strategy, associated with a fundamental principle for screening potential electrolyte additives coupling the Zn2+ ferrying effect with anion–π interaction, is put forward to construct a dendrite‐free, high‐ZUR Zn anode. By constructing the ion‐rich interface to retard the negative impact of the space charge layer, our Zn anode can endure ∼240 h continuous cycling at an ultrahigh ZUR of 87.3%.